Analisis kariotip beberapa kultivar aglonema=Karyotype Analysis of Several Cultivars of Aglaonema - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Aglaonema (Aglanema spp.) plants are grown and breed for their ornamental foliage. The objectives of this reseach were to identity the total chromosome number, morphology and chromosomes length of Aglaonema cultivars and to obtain phenetic relationship among Aglaonema cultivars based on karyotype analysis. Seven cultivars Aglaonema were used in this study, slides preparation of roor tips for chromosome observation were prepares according to aceto-orcein squash method. Karyotype data were collected, i.e chromosome numbers, length of the short and long arms of chromosomes, and absolute length of chromosomes. Another karyotype data recorded were intra and interchromosomal symmetry indexes of chromosomes, ratio of the longest to the shortes pairs of chromosmes and the chromosomes proportion having arms ratio up to 2,00. Phenetic relationship among several cultivars of Aglaonema had analysed based on karyotype data using cluster analysis. The result showed that Aglaonema spp. Cultivars had difference numbers of chromosomes and karyotype formulas. Cultivar 1 had 2 n = 7 x + 1 = 57, cultivar 2 and 5 had 2 n = 4 x + 2 + 2 = 36, cultivar 3, 6, and 7 had 2 n = 4 x = 32, cultivar 4 had 2 n = 7 x - 1 -1 = 54. Karyotype formula of cultivar 1 was 7 M 21 m 15 sm + 14 st. Cultivar 22 was 24 m + 10 sm 2 st, cultivar 3 was 22 M + 18 m + 12 sm, cultivar 4 was 7 m + 33 sm + 14 st, cultivar 5 was 24 m + 8 sm + 4 st, cultivar 6 was 20 m 8 sm 4 st.